2013
DOI: 10.1001/jama.2013.1625
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of 2 Doses of HPV Vaccine in Younger Adolescents vs 3 Doses in Young Women

Abstract: LOBALLY, CERVICAL CANCER IS the second most common cause of cancer morbidity and mortality in women. 1 Human papillomavirus (HPV) infection has been identified as a necessary cause for the development of cervical cancer, with HPV genotypes 16 and 18 accounting for approximately 70% of cervical cancer cases. Prevention of cervical cancer using either the bivalent (HPV-16 and HPV-18) or quadrivalent (HPV-6, HPV-11, HPV-16, and HPV-18) vaccine is the goal of immu-Author Affiliations are listed at the end of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
294
1
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(315 citation statements)
references
References 22 publications
9
294
1
8
Order By: Relevance
“…45,49 In another study, administration of a 2-dose regimen of qHPV vaccine in girls 9 to 13 years of age induced anti-HPV GMTs that were noninferior to those elicited by administration of a 3-dose regimen in young women 16 to 26 years of age. 50 This finding supports that a 2-dose regimen with the 9vHPV vaccine may be an acceptable alternative, which is currently under study. Another study was conducted to assess the safety of the 9vHPV vaccine in previous recipients of a 3-dose regimen of qHPV vaccine.…”
Section: Discussionsupporting
confidence: 68%
“…45,49 In another study, administration of a 2-dose regimen of qHPV vaccine in girls 9 to 13 years of age induced anti-HPV GMTs that were noninferior to those elicited by administration of a 3-dose regimen in young women 16 to 26 years of age. 50 This finding supports that a 2-dose regimen with the 9vHPV vaccine may be an acceptable alternative, which is currently under study. Another study was conducted to assess the safety of the 9vHPV vaccine in previous recipients of a 3-dose regimen of qHPV vaccine.…”
Section: Discussionsupporting
confidence: 68%
“…37 Accounting for those who do not complete the vaccine series would necessitate assumptions regarding vaccine efficacy and duration of protection for those who receive only one or 2 doses. [38][39][40] More complex models are better suited than ours for examining issues related to vaccine protection with less than 3 doses. 41 Instead, we used the simplifying assumption of 100% series completion not only to facilitate the use of our simplified model but also to allow for an easier interpretation of our results regarding the cost-effectiveness of 9vHPV compared with 4vHPV.…”
Section: Vaccine Characteristicsmentioning
confidence: 99%
“…Recent data indicates that immune responses to the vaccine are greater when initiated before adolescence [34,35]. In addition, HPV antibody titers measured after HPV vaccination in women aged 16-26 years have been shown to be lower than those in younger women [36][37][38][39]. While we did not ascertain prior HPV exposure (eg, by serological analysis) for subjects who entered the study having received at least 1 dose, the associations between the age at vaccination and risk of anogenital HPV6/11/16/18 infection and cervical cytological abnormalities did not appear to be due to differences in sexual experience at time of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Trials of extended dosing schedules (0, 12, and 24 months) have also shown lower antibody titers after vaccination, compared with shorter dosing schedules [34,36,37]. In addition, the number of vaccine doses and older age at vaccination have been shown to differentially influence T-and B-cell responses, respectively [34].…”
Section: Discussionmentioning
confidence: 99%